Nighthawking [large type] - Thomas, Russ, 1975- (Thorndike Press large print mystery series., 2021)
"Under the cover of night, a figure climbs over the wall of the Botanical Gardens. It's a dicey location in the populous city center, but they're on the hunt--only this time, the nighthawker unearths a body. Detective Sergeant Adam Tyler and his protégé, Detective Constable Mina Rabbani, are shunted onto the murder investigation. When the victim is identified as Chinese national from a wealthy family, in the UK on a student visa, the case takes a new urgency. As Tyler and Rabbani dig into the victim's life, it becomes clear there's more to her studies than meets the eye." --page [4] of cover